Granger causality analysis of deviation in total electron content during geomagnetic storms in the equatorial region - Sumitra Iyer (SpringerOpen, 2021)
Abstract The total electron content (TEC) in the ionosphere widely influences Global Navigation Satellite Systems (GNSS) especially for critical applications by inducing localized positional errors in the GNSS measurements. These errors can be mitigated by measuring TEC from stations located around the world at various temporal and spatial scales and using them for advanced forecasting of TEC. The TEC can be used as a tool in understanding space weather phenomena such as geomagnetic storms which cause disruptions in the ionosphere. This paper examines the causal relationship between perturbations in TEC caused by geomagnetic storms. The causality between two geomagnetic indices auroral electrojet (AE) and disturbed storm index (Dst) and TEC is investigated using Granger causality at two low-latitude stations, Bangalore and Hyderabad. The outcomes of this study strengthen the regional understanding and modeling of ionospheric parameters which can contribute towards the global efforts for modeling and reducing the ionospheric effects on trans-ionospheric communication and navigation. The causal inferences combined with the data-driven model can be useful in identifying the correct and informative physical quantities to improve the forecasting models.